Relationship Between Patient Satisfaction And Physician Characteristics. (December 2017) - Chen, J Gene; Zou, Baiming; Shuster, Jonathan
Background: Physician care influences patient satisfaction. Inherent physician attributes may also affect scores. Objective: To determine the relationship between physician characteristics and patient satisfaction regarding physician care and communication. Method: Observational retrospective study. We examined patient satisfaction surveys from inpatient adults across 9 questions (HCAHPS: Courtesy, Listen, and Explain; Press Ganey: Time, Concern, Informed, Friendliness, Skill, Rating) in relation to physician gender, age, ethnicity, race, and specialty. Results: We analyzed 51 896 surveys on 914 physicians. In univariate analysis, males were rated significantly more often in the highest category (top box) compared to females on Informed and Skill, and whites were rated in the top box more often than nonwhites on all questions. In multivariate analysis, there were no significant associations between ratings and physician gender, ethnicity, and race. On all questions, the odds of being rated in the top box were highest for obstetricians, second highest for surgeons, and lowest for medicine providers. On the question of Skill, the odds of being rated in the top box were higher with increasing age. Conclusion: Patient satisfaction regarding physicians is associated with physician specialty and age.